Exploring protein–protein ligation approaches for the cytosolic delivery of antigens using AIP56 - Pinheiro, Bruno; Moura, Ana C.; Oliveira, Pedro; Azevedo, Jorge E.; do Vale, Ana; dos Santos, Nuno M. S. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe intracellular delivery of biologics, particularly large cargoes like proteins, remains a challenge in biotechnology and biomedicine. The modular structure of well-characterized AB toxins allows different cargoes to be grafted, creating a target-specific biotechnological tool capable of cytosolic delivery.MethodsIn this study, we employed protein–protein fusion strategies—SpyCatcher003, SnoopCatcher, and SnoopLigase—to generate chimeras between the delivery region of AIP56 (AIP56L258-N497) and β-lactamase and performed functional delivery assays.ResultsThe chimeras were successfully obtained using these strategies and were all able to deliver β-lactamase into the cytosol of J774.A1 macrophages. Cellular fractionation showed that, although most of the β-lactamase remains associated with the endosomal compartment, an active portion is released into the cytosol.ConclusionAIP56 delivery region transporting other cargo directly to the cytosol of antigen-presenting cells might be a promising platform for antigen/cargo delivery. This study highlights the potential of protein–protein fusion strategies to create versatile, antigenically distinct toxin-based delivery systems for therapeutic applications.